How to enhance prediction of clinical outcomes in poor responders: integrating high-specific assays for anti-mullerian hormone with antral follicle count - Melado, Laura; Kumar, Ajay; Kalra, Bhanu; Kalafat, Erkan; Lawrenz, Barbara; Fatemi, Human (Frontiers in Endocrinology, 2025)
IntroductionAnti-Müllerian Hormone (AMH) and antral follicle count (AFC) are commonly used markers of ovarian reserve, yet their predictive accuracy in patients with low ovarian reserve remains limited. This study aimed to evaluate whether high-specific AMH assays targeting distinct molecular isoforms enhance the prediction of oocyte yield following ovarian stimulation (OS).MethodsA prospective observational study was conducted from February 2019 to December 2021 in a tertiary fertility center, including 72 women with low ovarian reserve (AMH <1.1ng/mL). On cycle day 2/3 before OS, Antral Follicle Count (AFC) and serum FSH, LH, estradiol, progesterone, and AMH levels were measured with the Elecsys assay (Roche). Frozen serum samples were analyzed with four high-specific AMH assays (AnshLabs, Texas): AL-196, AL-124, AL-105, and AL-133. Correlations were examined between AMH assays, AFC, and OS outcomes.ResultsPatients’ median age was 39 years, with AFC of 5.5 and median AMH-Elecsys of 0.64 ng/mL. All AMH assays correlated significantly with AFC and stimulation outcomes. The AL-196 assay showed the highest correlation with the number of follicles, cumulus-oocyte complexes (COCs), and metaphase II (MII) oocytes. Models combining AFC and AMH assays were strong predictors of COCs and MII oocytes, with AFC+AL-196 offering the best predictive value (Adjusted R2 = 0.474 for COCs and 0.485 for MII, p<0.001).ConclusionHigh-specific AMH assays using linear-epitope antibodies improve the accuracy of predicting oocyte yield in women with low ovarian reserve, thereby enabling more precise counselling and supporting personalized ovarian stimulation strategies.Clinical trial registrationNCT03826888.